(untitled) (Ibrahim Cardiac Medical Journal, 2022)
Critical appraisal of scientific publications is an important skill that must be acquired by the contemporary cardiologists. The preliminary step to a good critical appraisal is a sound understanding of the important aspects of a trial. In this issue of the Ibrahim Cardiac Medical Journal’s “Journal Scan”, we are first providing a brief summary of late-breaking randomised controlled trials published and presented at American College of Cardiology (ACC) Scientific Sessions 2021, and EuroPCR 2021, both of which were held virtually. We look at the important points to be derived from both potentially practice-changing trials, as well as key neutral trials of relevance in the above-mentioned meetings. In keeping with a critical appraisal format, each trial is introduced with its background and aims, PICO (Population, Intervention, Comparator, Outcomes) Criteria, main results and concluding remarks. Ibrahim Card Med J 2021; 11 (1): 86-95